Choosing induction chemotherapy in therapy-related acute myeloid leukemia. Issue 1 (March 2019) - Shea, Lauren K.; Uy, Geoffrey L.
Abstract: Patients with AML that develops after cytotoxic therapy (tAML) have overall inferior outcomes relative to de novo AML due to both patient-related factors and the intrinsic biology of the disease. Treatment of patients with tAML is challenging. The key initial clinical decision is whether a patient is a candidate for or likely to benefit from intensive induction chemotherapy, a determination which we argue should not be predicated on chronologic age alone. For those determined likely to tolerate intensive induction chemotherapy, CPX-351 is likely superior to conventional induction with cytarabine and daunorubicin. For those deemed inappropriate for intensive induction, hypomethylating agents have the strongest evidence base in elderly adults with AML, and are an attractive option in tAML. This is particularly true in patients with TP53 mutations who are less likely to respond to conventional induction chemotherapy. Exciting options on the therapeutic horizon for tAML include combination therapies incorporating BCL2 inhibitors, Hedgehog pathway inhibitors, and isocitrate dehydrogenase inhibitors.